The Evolution and Growth of Nearby Galaxy Groups - Fosdick, Katiya Claire (Proceedings of the Wisconsin Space Conference, 2020)
<span id="docs-internal-guid-2509acdc-7fff-5f7b-901f-da22303ece85" style="font-size: 10pt; font-family: 'Times New Roman'; color: #000000; background-color: transparent; font-weight: 400; font-style: normal; font-variant: normal; text-decoration: none; vertical-align: baseline; white-space: pre-wrap;">To determine how galaxy groups grow and individual galaxies evolve in the local universe, this project used 19 high-richness, high-mass galaxy groups at z < 0.1 from the Berlind et al. 2006 paper to study the nearby group environment through its optical properties. Using position, g-r color, and r-band absolute magnitude data, the shapes, luminosities, and colors of each member galaxy was mapped in group combination plots and an inter-group color-magnitude diagram of all 477 sample galaxies. These figures show that members of the high-mass group environment trend towards redness where the most luminous members of each galaxy group are found to be red. Both findings are consistent with previous predictions of the group environment’s bias towards red elliptical galaxies. Future work using optical properties and the galaxy sequence will be crucial to identify galaxies in groups undergoing evolutionary change as potential indicators of a changing group environment.